Análisis de cumplimiento de las NIIF en la cuenta 1540 “flota y equipo de transporte” en los estados financieros 2018 – 2019 de la empresa hotel Villa Rosa Linda del Llano - Villavicencio Meta. (2020)
The present article deals with the comparison between the processes and rulings used by the company known as Hotel Villa Rosa Linda Campestre in the Flota y Equipo de transporte account, acknowledged as a fixed asset. It also deals with the documentación of the company, the analysis of such information and the relevance of this research. The main goal of this research is to determine the ways the company carries its accounting processes, how they are applied and if the information it is using is updated or are held under the International Financial Reporting Standards (IFRS). Complications arise from the fact the company uses incorrect methods to measure its assets, it does not take into account the regulations proposed by National Government through its Estatuto Tributario (Tax Statute) and by the IFRS as proposed by the IASB, which may involve drawbacks when trying to have real accounting information, and in consequence, might create passive contingents or unexpected losses. Taking the aforementioned into account, it is advised to the company to abide the measures imposed by the previously mentioned institutions and additionally to apply them. In this way, it will create an accounting precedent, it will show its active assets reality and will generate a culture of good use of adequate rulings, in order to be an example for the rest of national and international entities, given that the latter ones have close contact with the Hotel.